Serum protein electrophoresis in 26 dogs with chronic hepatitis. (July 2022) - Gori, Eleonora; Pierini, Alessio; Tulone, Fiorenza; Abramo, Francesca; Marchetti, Veronica
Serum protein electrophoresis (SPE) shows the distribution of protein fractions, helping clinicians to characterize some pathologic processes. Information is lacking in the literature about SPE alterations in dogs with chronic hepatitis (CH). Our aim was to describe SPE alterations in canine CH, to compare SPE results to histologic scores, and to study SPE trends during follow-up. We reviewed retrospectively case data from dogs with a histologic diagnosis of CH. Only cases with SPE, CBC, and serum chemistry results available were included. Dogs were divided into subgroups based on histologic necroinflammatory activity (A) and fibrosis (F) scores (groups A0-1 and A>1; groups F<2 and F≥2). We included 26 dogs; 15 had follow-up SPE. The most common SPE alterations at admission were hypoalbuminemia ( n = 16), increases in α1-globulins ( n = 11), γ-globulins ( n = 11), α2-globulins ( n = 8), β2-globulins ( n = 7), and β1-globulins ( n = 6), and decreased albumin:globulin (A:G) ratios ( n = 20). Four of 11 dogs had β-γ bridging. Groups with higher A and F scores had higher β2-globulins. Eleven of 15 dogs with a post-treatment SPE had a decrease in γ-globulins and increase in A:G ratio compared to their T0, although there was no statistically significant difference. Although further studies are warranted, SPE may be useful for monitoring canine CH.